Yellow ZnxNi1−xWO4 pigments obtained using a polymeric precursor method - Oliveira, André Luiz M. de (2007)
New tungstate-based ceramic pigments, displaying ZnxNi1 xWO4 stoichiometry, were obtained at low temperature using a polymeric precursor method. The powder precursors were milled in an attritor mill in an alcoholic medium and heat treated for 12 h, yielding homogeneous and crystalline powder pigments. Characterization (TG/DTA, XRD, IR and colorimetry) showed that mass loss increased with increasing Zn contents. Despite the presence of secondary phases and impurities, the wolframite phase was present in all samples. IR analysis revealed bands related to MeeO and [WO6]6 group stretching was observed. The intensity of the yellow color of the pigments increased with increasing amount of nickel